2003
DOI: 10.1002/ccd.10617
|View full text |Cite
|
Sign up to set email alerts
|

Sonotherapy, antirestenotic therapeutic ultrasound in coronary arteries: The first clinical experience

Abstract: We studied the safety and feasibility of intracoronary sonotherapy (IST) and its effect on the coronary vessel at 6 months. Thirty-seven patients with stable or unstable angina were included (40 lesions). The indication was de novo lesion (n = 26), restenosis (n = 2), in-stent restenosis (n = 11), and a total occlusion of a venous bypass graft. After successful angioplasty, IST was performed using a 5 Fr catheter with three serial ultrasound transducers operating at 1 MHz. IST was successfully performed in 36 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…19,20 Prior to this randomized trial, two clinical registries took place and one has been formally published in a peer-reviewed journal. 13 This study reported a restenosis rate of 25% in a population receiving a stent with an average length of 23 mm. The apparent absence of effect in this registry should have been more critically considered before engaging in two medium-sized randomized trials in Europe and in the USA.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…19,20 Prior to this randomized trial, two clinical registries took place and one has been formally published in a peer-reviewed journal. 13 This study reported a restenosis rate of 25% in a population receiving a stent with an average length of 23 mm. The apparent absence of effect in this registry should have been more critically considered before engaging in two medium-sized randomized trials in Europe and in the USA.…”
Section: Discussionmentioning
confidence: 97%
“…13 However, this observational study did not address the ef®cacy of this new modality of treatment in a randomized fashion. The purpose of the present study therefore, is to evaluate the short-term and long-term safety and ef®cacy of intravascular sonotherapy in patients, when given immediately following de novo stenting.…”
Section: Introductionmentioning
confidence: 99%
“…Intravascular sonotherapy has demonstrated its efficacy in the prevention of neointimal hyperplasia after stent implantation (28). In addition to its capability in decreasing cellular proliferation (29), there is new evidence of a positive effect of intravascular sonotherapy on cell recovery through the …”
Section: Interventions To Promote Endothelializationmentioning
confidence: 99%
“…Intravascular high intensity ultrasound transducers in the 1 MHz frequency range have been realized for therapy purposes. 39,40 These will be suitable to deliver a local pushing field that is pointed radially outward from the catheter by definition and eliminates the need for extracorporeal excitation.…”
Section: Experimental Realization Of Alementioning
confidence: 99%